Enablers of research culture formation among teachers: A structural equation modeling - Wan Mohd Khairi, Wan Ibrahim; Suhaidah, Hussain; Azim Azuan, Osman (Global Academic Excellence (M) Sdn Bhd (GAE), 2025)
This study investigates the factors influencing the development of research culture in Malaysian secondary schools, focusing on the roles of transformational leadership, monetary backup, research equipment, and teachers’ instructional load. Grounded in the Resource-Based View (RBV) framework, the research conceptualizes schools as organizations reliant on both tangible and intangible resources to promote sustainable innovation. Using a quantitative cross-sectional survey design, data were collected from 198 secondary school teachers across various regions of Malaysia. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the hypothesized relationships. The results reveal that transformational leadership is the most significant and positive predictor of research culture among teachers. In contrast, monetary backup and instructional load did not exhibit statistically significant direct effects. Research equipment demonstrated a marginally significant positive influence, suggesting that adequate infrastructure may play a supporting role. The model explained 64.8% of the variance in research culture, highlighting the importance of leadership-driven strategies in cultivating inquiry-based practices. These findings contribute to theory by extending RBV into school settings and offer practical insights for education policymakers and administrators seeking to strengthen research engagement in schools.